Modelo de planejamento financeiro integrado ao planejamento estratégico pessoal - Schimith, Cristiano Descovi (2013)
Personal financial planning is a field of study that has been highlighted in recent times, especially when observed some periods of economic and financial uncertainty involving the global market, and that end directly impacts in life of people's. The main objective of this study is to propose a model of Personal Financial Planning. As for nature research is qualitative, exploratory and descriptive, making use of literature review to describe a model of organizational Strategic Planning, and Personal Strategic Planning, which served as the basis for structuring the proposed model. The conceptual basis is constructed through an analysis and description of the methodologies used by authors who are references in the financial field. The proposed model is composed of three stages: assessment, formulation and implementation. The stages consist of five steps interconnected through of feedback, and are subdivided into financial diagnostic, financial goals, internal aspects, external and actions. As a result of the study is presented the proposed model, has the potential to serve as support would improve the financial performance of individuals and can also serve as a tool to support professional consulting and financial coaching.